Modelling of Electrically Excited Synchronous Machine (EESM) considering nonlinear material characteristics and multiple saliencies - Seilmeier, Markus (2011)
Sophisticated control techniques for electrically excited synchronous machines need precise, but easy models. Non-ideal characteristics may appear, if the machine shows multiple geometric and/or saturation induced saliencies. In contrast to the conventional modelling approach, a novel stator-oriented magnetic circuit approach is used to deduce a nonlinear machine model with time-variant parameters, which makes it possible to account for multiple geometric and saturation induced saliencies systematically. Using this method one can find systematic conditions whether the cross saturation effect can occur. Moreover the new modeling technique leads to new insights for the interpretation of the resulting differential equations in the field oriented coordinates. One finds that both the differential and absolute inductances are relevant for torque generation in the machine.
Keywords: "Modelling"; "Synchronous Motor"; "Electrical Machine"; "AC machine"